Among the Scientologists: History, Theology, and Praxis, by Donald A. Westbrook. - Gregorius, Fredrik (2019)
Among the Scientologists: History, Theology, and Praxis, by Donald A. Westbrook. Oxford University Press, 2019. 332pp. Hb $45.00/£29.99. ISBN-13: 9780190664978.
Keywords: L. Ron Hubbard; New Religious Movements; Scientology; Rezension